Expression and Isolation of Recombinant Microneme 3 (MIC3) Protein of Toxoplasma gondii Local Isolate on Eschericia coli (BL21) - Indrasanti, D; Haryanto, A; Artama, WT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. Toxoplasmosis is a disease that infects all warm-blooded animals, including livestocks and humans caused by Toxoplasma gondii parasites. There are major drugs used for the therapy, though they have some effects to the patients, such as allergy, toxic and teratogenic for fetus. In addition, toxoplasmosis treatment is only effective for tachyzoites T. gondii in acute infection, while tissue cysts cannot be eradicated in chronic toxoplasmosis Tissue cysts of T. gondii contained in meat that are consumed by humans and meat-derived products may be important sources of infection for humans. Microneme protein (MIC) is one of proteins that belongs to excretory-secretory antigens (ESAs) of Toxoplasma gondii. Microneme 3 protein (MIC3) is the protein that plays an important role in the invasion process during cell infection as a mediator attachment parasite to the host cell. Recombinant MIC3 protein has been already used for the detection of toxoplasmosis and it could induce humoral and cellular immune response in experimental animals. The aim of this research was to express MIC3 recombinant protein of T. gondii from local isolate that was cloned into expression vector and transformed to E. coli BL21. In the future, recombinant protein MIC3 can be used for vaccine candidate and diagnostic tools for toxoplasmosis in animals and humans. Gene of MIC3 T. gondii local isolate (1.2 Kbp) was cloned into expression vector pET-32a(+) (5.9 Kbp) and transformed to Escherichia coli BL21. Protein from plasmid recombinant (7.1 Kbp) was expressed and performed by culturing recombinant bacteria into LB medium containing ampicillin and IPTG. Recombinant protein was isolated by sonication method and identified using SDS-PAGE. Finally, the recombinant protein was analyzed by immunoblotting using anti-ESAs polyclonal antibody. In conclusion, expression of the MIC3 gene with 108 kDa has been successfully performed by cloning gene encoding for MIC3 protein of T. gondii local isolate that can be identified with polyclonal antibody anti-ESAs.Key Words: Toxoplasma gondii, expression, MIC3 protein